Arabic Online Course Program Management on Ahlan Course - Syafiyatul Maf'udah; Alfan Sujefri; Nur Kholid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
One of the informal learning platforms in Arabic learning is learning courses. The online Arabic course program has a rapid development during the Covid-19 pandemic until now. This wascreated to support Arabic language learning which is carried out at home. Users of this learning service certainly have quite a lot of enthusiasts. Therefore it certainly has special program management to control the activities that take place in it. This research intends to find out how the management process is in this program and analyze the problems faced. The method used is a qualitative approach. Data collection techniques in the form of interviews, observations, and documentation. The results showed that the management in this course has 4 stages in the form of 1) planning; establishment of programs and materials taught, 2) organization; establishment of course schedules and preparation of evaluations and assessments, 3) implementation; providing motivation and guidance between coaches and teachers, teachers and students, as well as communication related to problems on social media, 4) control; evaluation and refinement of the curriculum used in the course.